Fostering Openness in Education: Considerations for Sustainable Policy-Making - Atenas, Javiera; Havemann, Leo; Nascimbeni, Fabio; Villar-Onrubia, Daniel; Orlic, Davor (Open Praxis, 2019)
This paper reviews a framework to support the co-creation of policies to sustainably foster Open Education. The framework has been derived from a comprehensive review of public and Open Education policy documents and related literature, as well as identification and consideration of contiguous issues in the education landscape that directly impact openness and can potentially derail policies, including datafication, copyright reforms, and the unbundling of services into component parts. The open policy framework, along with a canvas and set of change cards and a dynamic grounded in the participation and co-creation standard developed by the Open Government Partnership, have been used in three workshops piloted during 2018, to facilitate co-design of Open Education policies, by discussing contexts, objectives and challenges with policymakers and advisors both at national and institutional levels, policymakers and advocates with a series of tools and advise to enable arenas to co-create open-education policies.
Keywords: open education; educational policy; copyright reform; open learning recognition; Emerging